Từ điển chính tả tiếng Việt thông dụng - Nguyễn, Trọng Báu. (Hà Nội : Nhà xuất bản Khoa học xã hội, 2004)
Vietnamese dictionary of dictation.
Includes bibliographical references (p. 609-610).
Keywords: Vietnamese language -- Orthography and spelling -- Dictionaries